Inorganic binders and methods thereof

By adding carboxylated polymer and catechol wetting agent to the inorganic binder, the problem of low viscosity of alkali metal silicate in aqueous solution is solved, and higher bond strength and flexibility are achieved, ensuring the stable installation of the pollution control device components.

CN119604593APending Publication Date: 2025-03-113M INNOVATIVE PROPERTIES CO
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380056102.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-26
Filing Date
2023-07-26
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When alkali metal silicates act as inorganic binders, they have low viscosity in aqueous solution, resulting in adhesive penetration into the fiber mat and reducing bond strength and flexibility.

Method used

Adhesive compositions containing carboxylated polymers and catechol wetting agents are employed to increase viscosity and improve coating stability, prevent adhesive penetration, and maintain bond strength and flexibility.

Benefits of technology

It effectively improves the viscosity of the adhesive and the stability of the coating, enhances the bonding strength and flexibility, and ensures the stable installation and durability of the pollution control device components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604593A_ABST
    Figure CN119604593A_ABST
Patent Text Reader

Abstract

An adhesive composition and related components and methods are provided. The adhesive composition comprises a mixture of: an alkali metal silicate; a polycarboxylate; and catechol. When applied to a fibrous surface, the use of a combination of a carboxylated polymer and a catechol wetting agent can increase viscosity and prevent binder penetration while also reducing the surface tension of the solution to promote coating stability.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention provides an inorganic adhesive composition, which can be used to bond pollution control device components. Background Art

[0002] Catalysts have been used since the mid-1970s to reduce emissions of toxic pollutants such as carbon monoxide and hydrocarbons from engine exhaust. These catalysts promote the oxidation of these compounds into carbon dioxide and water, and are housed within pollution control devices known as catalytic converters. Advanced catalysts are able to reduce nitrogen oxide emissions to nitrogen, and these catalysts are found in three-way converters that are able to tackle all of these pollutants. Catalytic converters are incorporated into the exhaust systems of cars and other vehicles. In jurisdictions that have regulations on exhaust emissions, these have been effectively mandated for use on gas-powered vehicles.

[0003] Other pollution control devices may include catalytic monoliths, ceramic filters for diesel particulate filters (DPFs), and ceramic filters for gasoline particulate filters (GPFs). These devices require a structure to secure the device within a metal housing that is in turn connected to the exhaust system. The retention of the mounting assembly is typically dependent on a friction fit or, in some cases, an adhesive. It is often necessary to secure the converter to the automotive exhaust system over a very wide temperature range. Summary of the invention

[0004] An inorganic adhesive coating applied to the mounting mat between the pollution control device and its metal housing may be advantageously used. Alkali metal silicates such as sodium silicate, potassium silicate or lithium silicate may be used as inorganic binders. These materials may be activated by heating even after being substantially dried on the bonding surface. This property is particularly convenient in certain applications because it allows bonding closure after mat assembly without regard to processability or setting time. However, there are technical challenges in using alkali metal silicates as inorganic binders on fiber bonding surfaces (such as mat mountings for catalytic converters).

[0005] The inventors have found that alkali metal silicates tend to have low viscosities when applied from aqueous solutions. As a result, these compositions will penetrate deeply into the fiber mat after the coating operation, thereby reducing the amount of adhesive present on the surface. Surface interactions between the solution and the inorganic fibers may also result in the solution being readily wicked into the mat material. This has the undesirable effect of not only reducing bond strength, but also reducing the flexibility of the mat and making the mat mount less compressible.

[0006] The provided adhesive composition can solve all of these technical problems at the same time. The provided adhesive composition includes a carboxylated polymer that, when processed in an aqueous solution, increases viscosity and prevents penetration into the pad body when coated on a surface. The adhesive solution also contains a catechol wetting agent to reduce the surface tension of the solution and further improve coating stability. In addition, by maintaining flexibility and compressibility, the pad assembly coated with the adhesive can be easily wrapped around a ceramic monolith. After assembly, the pad mount can hold the ceramic monolith by maintaining a certain degree of compressibility before bonding. The ceramic monolith is brittle, so the flexibility of the pad can avoid accidental damage to the monolith during vehicle operation.

[0007] In a first aspect, the present invention provides an adhesive composition comprising a mixture of: an alkali metal silicate; a thickener comprising a polycarboxylate; and a wetting agent comprising catechol.

[0008] In a second aspect, a mounting mat assembly is provided that includes a fiber layer and an adhesive composition disposed on the fiber layer.

[0009] In a third aspect, a bonded assembly is provided and includes: a pollution control device; and a mounting mat assembly, wherein the adhesive composition bonds the fiber layer to the pollution control device. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 is a side cross-sectional view of a bonding assembly according to an exemplary embodiment.

[0011] FIG. 2A to FIG. 2D is a perspective view of a mounting pad assembly according to various exemplary embodiments.

[0012] Figures 3 to 7 is a side cross-sectional view of a partially bonded mounting pad assembly according to various exemplary embodiments.

[0013] Figure 8 is a schematic diagram illustrating an exemplary method of making a partially bonded mounting pad assembly.

[0014] Reference symbols used repeatedly in the specification and drawings are intended to represent the same or similar features or elements of the present disclosure. It should be understood that those skilled in the art can design many other modifications and embodiments that fall within the scope and essence of the principles of the present disclosure. The drawings may not be drawn to scale. DETAILED DESCRIPTION

[0015] As used herein, the terms "preferred" and "preferably" refer to embodiments described herein that may provide certain benefits under certain circumstances. However, other embodiments may also be preferred, under the same or other circumstances. In addition, the recitation of one or more preferred embodiments does not imply that other embodiments are not useful, and is not intended to exclude other embodiments from the scope of the present disclosure.

[0016] As used herein and in the appended claims, the singular forms "a", "an", and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a", "an" or "the" component may include one or more components known to those skilled in the art or their equivalents. Additionally, the term "and / or" means one or all of the listed elements or a combination of any two or more of the listed elements.

[0017] It is worth noting that the term "including" and its variations do not have a restrictive meaning when appearing in the attached specification. In addition, "one", "a", "the / said", "at least one" and "one or more" are used interchangeably herein. Relative terms such as left, right, forward, backward, top, bottom, side, upper, lower, horizontal, vertical, etc. may be used herein, and if so, they are from the perspective observed in the specific drawings. However, these terms are only used to simplify the description and are not intended to limit the scope of the present disclosure in any way.

[0018] References throughout this specification to "one embodiment," "certain embodiments," "one or more embodiments," or "an embodiment" mean that the particular features, structures, materials, or characteristics described in relation to the embodiment are included in at least one embodiment of the present disclosure. Thus, phrases appearing in multiple places throughout this specification (such as "in one or more embodiments," "in certain embodiments," "in an embodiment," or "in an embodiment") are not necessarily referring to the same embodiment of the present disclosure.

[0019] When describing the preferred embodiments of the present disclosure, specific terms will be used for clarity. However, the present disclosure is not intended to be limited to the specific terms so selected, and each term so selected includes all technical equivalents that play a similar role.

[0020] Reference Figure 1, an exemplary pollution control device according to the present disclosure is herein represented as bonding assembly 100. Bonding assembly 100 includes housing 120, pollution control element 140 mounted in housing 120, and mounting mat 160 disposed between pollution control element 140 and housing 120 to fix element 140 at a desired position within housing 120. Mounting mat 160 is not particularly limited, but is generally made of a fiber layer made of inorganic fibers.

[0021] Suitable inorganic fibers may include any of the fibers known and / or used in mounting mats for mounting pollution control devices. Useful inorganic fibers include, for example, glass fibers, ceramic fibers, non-oxide inorganic fibers (such as graphite fibers or boron fibers), and mixtures thereof. Particularly useful are ceramic fibers that can be obtained by a so-called sol-gel process, which are typically crystalline and therefore also referred to as polycrystalline fibers. Various useful inorganic fibers may include, for example, those disclosed in U.S. Patent Nos. 6,460,320 (Schierz et al.); 6,737,146 (Schierz et al.); and 7,033,412 (Kumar et al.).

[0022] Pollution control element 140 may be viewed within housing 120 by wrapping mat 160 around pollution control element 140 and then placing the wrapped element in the desired location within the housing, a process sometimes referred to as "canning." Mounting mat 160 is bonded to pollution control element 140 by adhesive layer 170. In this depiction, housing 120 includes a tapered inlet 130 through which exhaust gases flow into assembly 100 (see arrow A); and a tapered outlet 150 through which exhaust gases flow out of assembly 100.

[0023] Figure 2A The pad 160a and adhesive layer 170a isolated in the partially bonded assembly 162a are shown. The pad 160a can be conveniently pre-coated with the adhesive layer 170a. Such pre-coated configurations can then be provided to the original equipment manufacturer (OEM) or after-sales installer for final assembly. The pad 160a includes paired alignment features 164a, 164a', which interlock with each other when the pad 160a is wrapped around the pollution control element in a surrounding relationship. Specific features 164a, 164a' are only exemplary, and many alternatives are also possible, such as using other interlocking profiles or even separate fasteners (if necessary).

[0024] Optionally and as shown, adhesive layer 170a is not coextensive with mounting pad 160a. Figure 2AIn the embodiment of the present invention, the adhesive layer 170a is disposed on the pad in a discontinuous pattern, and more specifically in a striped pattern in this case. The stripes may be parallel to each other or may not be parallel to each other. If not parallel, at least some of the stripes may cross each other. In some embodiments, the adhesive layer 170a is represented by an array of repeated or randomized islands. In the case of being made of inorganic materials, the adhesive layer 170a can be relatively rigid depending on its thickness, and the adhesive layer may preferably have stripes that are axially oriented (as opposed to circumferentially oriented) to facilitate wrapping the pad 160a around a cylindrical object (such as the pollution control element 140) ( Figure 1 Where mounting pad 160a is shown in a planar configuration, adhesive layer 170a may be applied to mounting pad 160a according to any suitable two-dimensional pattern.

[0025] Figure 2B , Figure 2C and Figure 2D Other possible two-dimensional patterns of the adhesive layer are shown. For example, Figure 2B Partially bonded component 162b is shown having an adhesive layer 170b that is continuous and generally coextensive with a major surface of component 162b. Figure 2C A partially bonded assembly 162c is shown where the adhesive layer 170c is discontinuous and consists of a plurality of circular islands. Figure 2D A partially bonded assembly 162d is shown having an adhesive layer 170d comprised of parallel stripes and non-parallel stripes, wherein the stripes cross one another.

[0026] The composition for adhesive layer 170 can be prepared by a mixture of alkali metal silicate, polycarboxylate and catechol. At ambient temperature (e.g., about 21 ° C), adhesive layer 170 is solid in its final form. However, adhesive layer 170 is usually prepared by an aqueous solution in which alkali metal silicate, polycarboxylate and catechol are uniformly dispersed in water. The aqueous solution can then be applied to a pollution control element or a mounting pad, and water is removed to provide a solid adhesive layer. The aqueous solution is stable at ambient temperature, thereby allowing adhesive to be provided to end users (if necessary) in liquid form. These main components do not have to be unique, and other additives may also be included. Such additives may include, for example, dyes or pigments to help visually distinguish the position where the adhesive solution has been applied.

[0027] Other useful additives may include fillers for controlled soaking and viscosity control, and hardeners for increasing thermal durability. Examples of fillers may be fine particles of inorganic materials such as silica, alumina, mullite, zirconium oxide, magnesium oxide, and clay. Examples of hardeners include zinc oxide, zinc hydroxide, magnesium oxide, magnesium hydroxide, aluminum oxide, aluminum hydroxide, phosphates, and borates.

[0028] The alkali metal silicate may include sodium silicate, potassium silicate, lithium silicate, or a combination thereof. In some embodiments, the alkali metal silicate is sodium silicate. Sodium silicate, also known as water glass, is an inorganic compound containing anionic polymer chains composed of tetrahedral SiO4 units. The drying and curing process of an aqueous sodium silicate solution involves a condensation polymerization that combines two silanol groups generated by hydrolysis and releases a water molecule. Sodium silicate has a wide range of applications, including cement for making paperboard, water treatment, passive fire protection, and automotive repair. Most notably, it has high temperature performance and is fire-resistant and intumescent.

[0029] Alkali metal silicates are typically the main component of the adhesive and can be present in any suitable amount. The alkali metal silicate can be 40% to 99% by weight, 70% to 97% by weight, 85% to 95% by weight of the total solids weight of the adhesive composition, or in some embodiments, less than, equal to or greater than 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 97%, 98% or 99% by weight of the total solids weight of the adhesive composition.

[0030] Polycarboxylates or carboxylate polymers, when in their aqueous form, can be used as thickeners for adhesive compositions. Typically, these are water-soluble linear polymers and are characterized by their polar carboxylate groups (-COO - ) group. Simple polycarboxylates can be prepared as homopolymers of acrylic acid, copolymers of acrylic acid and maleic acid, maleic acid terpolymers, or any mixture thereof. As an example, polyacrylic acid has the following chemical structure:

[0031]

[0032] , where n can be any positive integer.

[0033] As another example, polymaleic acid has the following chemical structure:

[0034]

[0035] , where n can be any positive integer.

[0036] Useful polycarboxylates as thickeners in alkaline solutions include sodium polycarboxylates, potassium polycarboxylates, sodium carboxymethylcellulose, potassium carboxymethylcellulose, and combinations thereof.

[0037] Useful polycarboxylic acids (or their salts) include those with molecular weights ranging from 3000 g / mol to 1×10 7 g / mol, 10,000 g / mol to 8×10 6 g / mol, 1×10 5 g / mol to 6×10 6 g / mol, or in some embodiments, including molecular weights less than, equal to, or greater than 3000 g / mol; 4000 g / mol; 5000 g / mol; 7000 g / mol; 10,000 g / mol; 50,000 g / mol; 1×10 5 g / mol; 5×10 5 g / mol, 1×10 6 g / mol, 3×10 6 g / mol, 5×10 6 g / mol, 7×10 6 g / mol or 1×10 7 g / mol. One source of commercially available polyacrylic acid homopolymers that can be used in the present disclosure includes the ACUSOL 445 series from The Dow Chemical Company, Wilmington, DE, USA. Other commercially available polyacrylic acid homopolymers (and their salts) are ACUSOL 929 (10,000 MW) and ACUMER 1510 (60,000 MW), both of which are available from The Dow Chemical Company. Another commercially available polyacrylic acid is AQUATREAT AR-6 (100,000 MW) from Akzo Nobel, Amsterdam (AkzoNobel Strawinskylaan 2555 1077ZZ Amsterdam Postbus 75730 1070AS Amsterdam). Another commercially available polyacrylic acid is AQUALIC IH (3-5×10 6 MW).

[0038] As a thickening agent, polycarboxylates can increase viscosity and reduce the degree of adhesive penetration into the pad. Various conventional organic polymers can be used for this purpose, including polyvinyl acetate, polyethylene oxide, polyamines, etc. However, when combined with concentrated solutions of sodium silicate, these polymers tend to be insoluble. Advantageously, it has been found that some of the above-mentioned carboxylated polymers such as sodium carboxylate or sodium carboxymethylcellulose can remain completely soluble in alkaline solutions. The pH of such alkaline solutions with sodium silicate can be 9 to 13, 10 to 12, or in some embodiments, less than, equal to or greater than 9, 10, 11, 12 or 13.

[0039] Carboxymethyl cellulose is available in a variety of molecular weights. Low molecular weight carboxymethyl cellulose has an M of about 90,000 g / mol. w And its 2% solution will have a viscosity of about 1.1 cP at 25°C. Medium weight carboxymethyl cellulose has an M of about 250,000 g / mol. w High molecular weight carboxymethyl cellulose has an M of about 700,000 g / mol. w And a 2% solution at 25°C will have a viscosity of about 12 cP.

[0040] When the adhesive is an aqueous solution, the polycarboxylate can exist in any amount suitable for obtaining a desired texture or viscosity. The polycarboxylate can be 1 wt % to 30 wt %, 1.5 wt % to 20 wt %, 2 wt % to 10 wt % of the total solid weight of the adhesive composition, or in some embodiments, less than, equal to or greater than 1 wt %, 1.5 wt %, 2 wt %, 2.5 wt %, 3 wt %, 3.5 wt %, 4 wt %, 4.5 wt %, 5 wt %, 6 wt %, 7 wt %, 8 wt %, 9 wt %, 10 wt %, 11 wt %, 12 wt %, 15 wt %, 17 wt %, 20 wt %, 25 wt % or 30 wt % of the total solid weight of the adhesive composition.

[0041] Catechol is a diphenol compound comprising a benzene nucleus with two hydroxyl substituents arranged ortho to each other, and is the conjugate acid of catechol ester (catecholate). The basic chemical structure of catechol is as follows:

[0042]

[0043] Alkyl groups or other chemical groups can be covalently bonded to the aryl groups in the above structures to obtain more complex catechols.

[0044] In the provided adhesive compositions, catechols such as 4-tert-butylcatechol were found to be surprisingly effective wetting agents. Conventional surfactant wetting agents, such as polyoxyethylene alkyl ethers, may also be used, but it has been found that these wetting agents can adversely affect the bond strength of the inorganic adhesive after thermal curing. Empirical data have shown that catechols perform well as wetting agents, are easily soluble in alkaline solutions, and substantially avoid reducing the bond strength of the inorganic adhesive to a ceramic monolith (such as those made of cordierite).

[0045] The catechol component should be present in an amount to achieve optimal wetting properties of the aqueous adhesive composition on the mounting mat, which in turn depends on the surface characteristics of the mounting mat. For useful inorganic fiber mounting mats, the polycarboxylate may be from 0.05% to 10%, 0.1% to 5%, 0.15% to 2% by weight of the total solids weight of the binder composition, or in some embodiments, less than, equal to, or greater than 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.5%, 1.7%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight of the total solids weight of the binder composition.

[0046] Figure 3 Depicted is a partially bonded assembly 262, which illustrates the useful properties of the provided adhesive composition when applied to a mounting pad in an aqueous form. As shown in the cross-sectional view, the mounting pad 260 is coated with a discontinuous adhesive layer 270 along its top major surface 266, which is exposed on the top major surface 266 of the mounting pad 260. The thickness of the mounting pad can be application-specific and is not particularly limited, but typically has a thickness of 6 mm to 15 mm. The adhesive layer 270 can be applied according to any suitable pattern, as previously described with respect to the partially bonded assembly 162.

[0047] Reference again Figure 3, adhesive layer 270 has an exposed surface that is raised and covers some surface area of ​​mounting pad 260. At the same time, adhesive layer 270 also penetrates to some extent into mounting pad 260. The total thickness of adhesive layer 270 (including portions located above and below the plane of top major surface 266) can be 0.01 mm to 4.5 mm, 0.3 mm to 4.2 mm, 0.35 mm to 2.0 mm, or in some embodiments, less than, equal to, or greater than 0.01 micrometers, 0.05 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.35 mm, 0.4 mm, 0.5 mm, 0.7 mm, 1 mm, 1.2 mm, 1.5 mm, 1.7 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.2 mm, or 4.5 mm. The degree of penetration or portion of the overall thickness absorbed into the mounting pad can be from 0% to 28%, 0% to 25%, 0% to 20% of the total thickness of the adhesive layer 270, or in some embodiments less than, equal to, or greater than 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, or 30% of the total thickness of the adhesive layer.

[0048] Figures 4 to 7 An alternative configuration of the adhesive layer is shown in cross-section. Figure 4 An assembly 362 is shown having an adhesive layer 370 extending continuously across a mounting pad 360; Figure 5 An assembly 462 is shown in which an adhesive layer 470 is discontinuously disposed on both major surfaces of a mounting pad 460; Figure 6 An assembly 562 is shown in which the adhesive layer 570 is discontinuous on one major surface of the mounting pad 560 but is continuous on the opposite major surface thereof; and finally, Figure 7 Component 662 is shown having a continuous adhesive layer 670 extending across its two major surfaces. By having an adhesive layer on both major surfaces, the mounting pad can be Figure 1 The adhesive layer is arranged in such a way that it is adhesively bonded to both the housing and the pollution control element. Other options and advantages of the above-mentioned adhesive layer configurations have already been noted and will not be repeated.

[0049] Figure 8An exemplary method 802 of making a partially bonded assembly 862 is illustrated. In this method, a continuous web of mounting mat 860 is transported along a downstream direction D (as indicated) using a conventional conveyor belt system. Mounting mat 860 can be prepared according to any conventional technique (e.g., conventional wet-laid or dry-laid processes). As mounting mat 860 is conveyed downstream, a film, coating, or layer of adhesive 870 can be deposited onto the exposed top major surface 866 of mounting mat 860 by a roll coater 872.

[0050] The top major surface 866 of the mounting mat 860 is then exposed to an energy source 874, which activates the adhesive 870 on the top major surface 866 of the mounting mat 860. Such adhesive activation is performed, for example, by passing the web through hot air (e.g., in an oven, under a heat lamp, etc.); in contact with a heated surface; under an ultraviolet light source; or under an electron beam source, as desired to activate the adhesive. The resulting partially bonded mounting mat assembly can be formed (e.g., molded or laser cut) into individual mounting mats or alternatively wound into a roll for subsequent conversion into individually packaged mounting mats.

[0051] Example

[0052] Objects and advantages of the present disclosure are further illustrated by the following non-limiting examples, but the particular materials and amounts thereof recited in these examples, as well as other conditions and details, should not be construed to unduly limit the present disclosure. Where applicable, brand names and trade names are shown in all capital letters.

[0053] Table 1: Materials

[0054]

[0055]

[0056] Test methods and calculations

[0057] Coating Preparation - Basis Weight

[0058] Weigh 1180 grams per square meter (gsm) of 3M INTERAM Mat Mount 1450HR (3M Company, St. Paul, MN, United States) of 12 cm x 16 cm size. Apply the coating solution sample to the pad in rows along the width with a syringe. The lines are spaced 10 mm apart from each other, and the width, length, and thickness of the applied lines of the sample are visually checked for consistency. Approximately 16 lines are applied. The coated pad is then dried at 150°C for five minutes. The coated pad is then weighed. The average coating weight / area is calculated by subtracting the weight of the uncoated pad from the weight of the coated pad and then dividing by the coated area.

[0059] Coating stability

[0060] The coating solution samples were applied to a 3M INTERAM Mat Mount 1450HR of 12 cm x 16 cm size. The coating solution samples were applied to the pad in rows along the width with a syringe. The lines were spaced 10 mm apart from each other, and the sample was visually checked for consistency in width, length, and thickness of the applied lines. Approximately 16 lines were applied. A visual assessment was performed to determine if the coating solution was repelled from the pad surface. If the coating solution was not repelled during application, the coating stability was scored as acceptable. If the coating solution was repelled, the coating stability was scored as repelled.

[0061] Immersion depth

[0062] The coating solution samples were applied to a 3M INTERAM Mat Mount 1450HR of 12 cm × 16 cm size. The coating solution samples were applied to the pad in rows along the width with a syringe. The lines were spaced 10 mm apart from each other, and the consistency of the width, length, and thickness of the applied lines of the sample was visually checked. Approximately 16 lines were applied. The coated pad was then dried at 150°C for five minutes. The pad was cross-sectioned along the lines of the applied coating solution. The pad was then compressed to a thickness of about 7.2 mm. The coating depth in the pad was measured, and then divided by the pad thickness to calculate the immersion depth percentage.

[0063] Adhesion

[0064] Prepared by cutting a catalytic monolith (NGK Insulators, LTD, Aichi, Japan) along the cell Cordierite board. The surface of the board is polished to remove burrs and prepared as an adherend. The coating solution sample is uniformly applied to a 3M INTERAM MatMount 1450HR cut into a size of 50mm × 50mm. Visual inspection of the width, length and consistency of the thickness of the coating applied to the sample. The coated pad is placed on a cordierite board, compressed to a pad thickness of 5mm, and heat treated at 900°C for one hour. After heat treatment, the coated pad is peeled off from the board. Measure the area (length × width) of the coating sample visibly bonded to the board surface (A1) and the area (A2) of the coating sample that remains bonded to the pad surface. The bonding area ratio is calculated by dividing A1 by the sum of A1 and A2 and multiplying by 100.

[0065] Example 1 to Example 6 (EX1-EX6) and Comparative Example 1 to Comparative Example 5 (CE1-CE5)

[0066] The amounts of materials in grams were mixed as shown in Table 2. The basis weight of the coating solutions was also calculated and recorded in Table 2. It was observed that the solid components in all sample solutions except CE5 dissolved uniformly into the water to provide homogeneous solutions.

[0067] Table 2: Coating solution composition (in grams)

[0068]

[0069]

[0070] The tests were performed and the results are presented in Table 3.

[0071] Table 3: Coating solution test results

[0072]

[0073] All references, patents and patent applications cited in the above patent applications are incorporated herein by reference in their entirety in a consistent manner. In the event of inconsistency or conflict between the incorporated references and the present application, the information in the foregoing description shall prevail. The foregoing description, which is given to enable a person of ordinary skill in the art to practice the present disclosure protected by the claims, should not be construed as limiting the scope of the present disclosure, which is defined by the claims and all equivalents thereof.

Claims

1. An adhesive composition comprising a mixture of the following substances: Alkali metal silicates; Polycarboxylates; and Catechol. 2 . The adhesive composition according to claim 1 , wherein the alkali metal silicate comprises sodium silicate, potassium silicate, lithium silicate, or a combination thereof. 3 . The adhesive composition according to claim 1 , wherein the polycarboxylate comprises sodium polycarboxylate, potassium polycarboxylate, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, or a combination thereof.

4. The adhesive composition of claim 1, wherein the catechol comprises 4-tert-butylcatechol. 5 . The adhesive composition of claim 1 , wherein the alkali metal silicate is present in an amount of 40 wt % to 99 wt % relative to the total solid weight of the adhesive composition.

6. The adhesive composition of claim 1, wherein the polycarboxylate is present in an amount of 1 wt% to 30 wt% relative to the total solid weight of the adhesive composition. 7 . The adhesive composition of claim 1 , wherein the catechol is present in an amount of 0.05 wt % to 10 wt % relative to the total solid weight of the adhesive composition.

8. The adhesive composition according to claim 1, wherein the adhesive composition is a solid coating. 9 . The adhesive composition according to claim 1 , further comprising water, wherein the alkali metal silicate, polycarboxylate and catechol are uniformly dispersed in the water.

10. A mounting mat assembly comprising a fiber layer and the adhesive composition of claim 1 applied on the fiber layer.

11. The assembly of claim 10, wherein the adhesive composition is disposed on the fiber layer in a discontinuous pattern.

12. The assembly of claim 10, wherein 0% to 28% of the total thickness of the adhesive composition is absorbed into the fiber layer.

13. A bonding assembly, comprising: pollution control devices; and The mounting mat assembly of claim 1, wherein the adhesive composition bonds the fiber layer to the pollution control device.

14. The bonded assembly of claim 13, wherein the pollution control device comprises a catalytic monolith, a ceramic filter for a diesel particulate filter (DPF), or a ceramic filter for a gasoline particulate filter (GPF).

15. The bonded assembly of claim 13, further comprising a housing also bonded to the mounting mat by the adhesive.

Citation Information

Patent Citations

  • Yarn which expands upon heating, and method for its manufacture

    US6460320B2

  • Bedding mat for supporting an exhaust gas catalyst

    US6737146B2

  • Exhaust gas treatment device and method for making the same

    US7033412B2